Ergogenic Effects of β-Alanine Supplementation on Different Sports Modalities: Strong Evidence or only Incipient Findings? - Brisola, Gabriel M.P. [UNESP]; Zagatto, Alessandro M. [UNESP] (Wolters Kluwer, 2019)
Brisola, GMP and Zagatto, AM. Ergogenic effects of β-alanine supplementation on different sports modalities: strong evidence or only incipient findings? J Strength Cond Res 33(1): 253-282, 2019 - β-Alanine supplementation is a popular nutritional ergogenic aid among the sports community. Due to its efficacy, already proven in the literature, to increase the intramuscular carnosine content (β-alanyl-L-histidine), whose main function is intramuscular buffering, β-alanine supplementation has become a nutritional strategy to improve performance, mainly in high-intensity efforts. However, although many studies present evidence of the efficacy of β-alanine supplementation in high-intensity efforts, discrepancies in outcomes are still present and the performance enhancing effects seem to be related to the specificities of each sport discipline, making it difficult for athletes/coaches to interpret the efficacy of β-alanine supplementation. Thus, this study carried out a review of the literature on this topic and summarized, analyzed, and critically discussed the findings with the objective of clarifying the current evidence found in the literature on different types of efforts and sport modalities. The present review revealed that inconsistencies are still found in aerobic parameters determined in incremental tests, except for physical working capacity at the neuromuscular fatigue threshold. Inconsistencies are also found for strength exercises and intermittent high-intensity efforts, whereas in supramaximal continuous mode intermittent exercise, the beneficial evidence is strong. In sports modalities, the evidence should be analyzed separately for each sporting modality. Thus, sports modalities that have strong evidence of the ergogenic effects of β-alanine supplementation are: cycling race of 4 km, rowing race of 2,000 m, swimming race of 100 and 200 m, combat modalities, and water polo. Finally, there is some evidence of slight additional effects on physical performance from cosupplementation with sodium bicarbonate.
Keywords: carnosine; high-intensity efforts; intramuscular buffer; nutritional; physical performance; review